Teachers' classroom practices and content knowledge as predictors of civic competence of senior secondary school students in Ibadan (2019)
Abundant literature affirms students' low level of civic competence, especially ai the primary and junior secondary school levels. This study was embarked upon to determine teachers' classroom practices and content knowledge as predictors of senior secondary school students' civic competence (knowledge, disposition, and engagement) in Ibadan. Expo facto research design was adopted for the study with four hundred and fifty (450) students and fifteen (15) Civic Education teachers as participants. The instruments employed were Civic Education Teachers' Classroom Practices Observational Scale (CETCPOS), Measuring Guide for Teachers' Classroom Practices Observational Scale (MGTCPOS), Civic Education Teachers’ Content Knowledge Questions (CETCKQ), Students' Civic Knowledge Achievement Test (SKAT), Students' Civic Disposition Questionnaire (SCDQ), and Students' Civic Engagement Questionnaire (SCEQ). One major research question was raised and answered at 0.05 level of significance. Data were analyzed using mean and Pearson Product Moment Correlation (PPMC). The findings of the study revealed no correlation between students' civic competence and teachers' classroom practices and their civic knowledge. Improved teachers' knowledge in Civic Education and classroom practices were observed, although without effects on the civic competence of students. It was recommended that government, school administrators and parents' factors be subsequently studied, and that evaluation of Civic Education should include behavioural assessment.